FORMATION OF HUMAN RESOURCES IN THE ENTERPRISE’S COMPETITIVENESS MANAGEMENT SYSTEM DURING THE POST-WAR ECONOMIC RECOVERY - SEMYKINA, Maryna; ZAPIRCHENKO, Liudmyla; NISFOYAN , Sergiy; SEMYKINA, Anna (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This article focuses on substantiating the theoretical and applied foundations for developing human resource potential as a strategic tool for enhancing enterprise competitiveness within the context of post-war economic reconstruction. It proposes understanding the essence of human resource potential in the context of post-war economic development as an integrated capacity of enterprise employees for effective activities aimed at production recovery, adaptation to new conditions, innovative development, ensuring competitiveness, and demonstrating social responsibility. It is demonstrated that the structure of enterprise human resource potential undergoes changes in the context of post-war economic reconstruction: in addition to traditional structural components such as personal, professional-qualification, organizational-managerial, and innovative potentials, components such as adaptive potential, psychological resilience, social cohesion, and responsibility become increasingly important. The factors influencing the development of human resource potential at the post-war stage are identified and systematized according to a number of classification criteria (by content, level, nature, duration of impact). Scientific and practical recommendations for evaluating human resource potential are developed, and the presence of a systematic correlation between its efficiency indicators and the long-term competitive advantages of the enterprise is substantiated. Directions and mechanisms for developing human resource potential and enhancing its competitiveness are identified. A model of strategic management for developing the enterprise’s human resource potential in the context of post-war economic reconstruction is proposed, emphasizing the importance of systemic planning, innovation, and social stability for the successful recovery of enterprises and ensuring their long-term sustainability.